The Impact of Covid 19 Concerns on the Mental Health of Athlete Students with the Modifying Role of Social Support in a Multi-Group Analysis by Gender - Faezeh Abdolahnezhad (Qom University of Medical Sciences, 2021)
Background and Objectives: Coronavirus Disease (2019) (COVID-19) not only threatens the physical health of individuals but also causes multiple mental conditions. This study aimed to investigate the impact of COVID-19 concerns on student-athletes chr('39') mental health with the modifying role of social support. Methods: This descriptive-correlational study was conducted using the field research method and gender-based multi-group analysis. The statistical population consisted of student-athletes from Region 9 of Iran. Using G*Power, the statistical sample was determined to be 146 subjects who were selected by simple random sampling technique. The Keyes Mental Health Questionnaire (2006) and the Social Support and COVID-19 Concerns Questionnaire (Graupensperger, 2020) were used to collect the required data after their validity and reliability were confirmed. The collected data were analyzed using the Partial Least Square (PLS) method. Results: The study data revealed that COVID-19 concern presents a significant negative impact on student-athletes’ mental health. Social support also played a modifying role in the relationship between COVID-19 concern and the examined subjects’ mental health and undermined this relationship. Moreover, the PLS-MGA results revealed no gender-wise significant difference in this respect. Conclusion: Concerns about COVID-19 adversely affect studentschr('39') mental health. Additionally, social support can positively influence this population’s mental health and reduce the negative impact of COVID-19 disease on their mental health.